Influence of addition of different cereal and leguminous flours on spawngrowth of Pleurotus ostreatus - Dipanshi Thakur; Sud, Deepika; Riya; Banyal , D. K.; Bhardwaj, Neelam (Mushroom Research, 2024)
Oyster mushroom is most widely cultivated mushrooms in the world. Spawn production is a crucial part of the mushroom-growing process. The experiment was conducted to determine the effect of different organic additives cereal and leguminous flour of rice, wheat, maize, gram, chickpea, lentil, soybean and black gram at different concentrations (2, 4 and 6%) on spawn growth of Pleurotus ostreatus. The results revealed that among cereal flours the maximum Mycelial Run Rate (MRR) was observed at 6% wheat flour (10.95 mm day-1) as compared to other treatments and took 11 days  and followed by 2% rice flour (10.47 mm day-1) which required 13 days for complete mycelial growth. In case of leguminous flours, the MRR  at 2% gram and 4% black gram flour (9.26 mm day-1) were statistically on par with each other which was highest among all other treatments followed by 2% soybean flour (8.33 mm day-1) and took 13 days for complete mycelial growth, whereas other additives took more than 15 days. Out of all tested additives, 6% wheat flour gave the maximum MRR as well as took lesser time to complete mycelial growth as compared to other additives. The least      MRR was observed in control (6.96 mm day-1) on 15th days which was significantly lower than all other treatments which indicates that addition of supplements enhances the spawn growth and minimizes the days of spawn growth.